EFFECT OF MECHANICAL PROPERTIES ON SURFACE TREATMENT TO CARBON FIBER WOUND HDPE COMPOSITE PIPE (CFWHCP) - Mohd Husni, Muhammad Amir Azri (2018)
Currently, the pipeline used in oil and gas is metallic material. However, these materials is having a problem with corrosion and erosion. The other alternative is to use the non-metallic pipe as it is free from corrosion and erosion. The suitable alternative is HDPE pipe because it has greater strength compared with other non-material. To enhance the strength of HDPE pipe, the surface of HDPE pipe is wind with carbon fiber to produce Carbon Fiber Wind HDPE Composite pipe (CFWHCP). This project is to study the effect of surface treatment of HDPE pipe before winding process to mechanical properties of CFWHCP and evaluate the surface treatment which shows significant improvement to its mechanical properties. Two HDPE composite pipe is wound by carbon fiber with winding angle of 57° and epoxy as it matrix. The CFWHCP for both specimen is fixed for 6 fiber tows and same size which is 12k. One of HDPE pipe surface of CFWHCP did not been grinded and have a smooth surface named as Sample 1.The surface of the other HDPE pipe for one of the CFWHCP is been grinded with sandpaper grade 60 before proceed with carbon fiber wound with epoxy to have a rough surface named Sample 2. Both of it undergo the axial tensile test and apparent hoop test in order to get the mechanical properties. The findings show that Sample 2 is 9.4% greater tensile strength which is 28.19 MPa while Sample 1 has 25.77 MPa for axial tensile test. For apparent hoop test, Sample 2 is only 0.94% greater than Sample 1 as it tensile strength is 3.21 MPa and Sample 1 is 3.18 MPa. It can conclude that Sample 2 which having surface treatment at HDPE pipe before winding with carbon fiber has a better tensile strength due to the better matrix bonding and better grip of carbon fiber with HDPE pipe.